Why do lactobacilli dominate the human vaginal microbiota?. (7th November 2016) - Witkin, SS; Linhares, IM
Abstract : Lactobacilli are the most abundant vaginal bacteria in women. They inhibit binding of other bacteria to epithelial cells and produce lactic acid that kills or inhibits the growth of many other bacteria. Lactic acid blocks histone deacetylases, thereby enhancing gene transcription and DNA repair. Lactic acid induces autophagy in epithelial cells to degrade intracellular microorganisms and promote homeostasis. Lactobacilli are tolerated by vaginal epithelial cells and inhibit induction of pro‐inflammatory cytokines. Emotional stress may reduce lactobacilli abundance in the vaginal microbiota and enhance inflammation. The ability of lactobacilli to inhibit infection without inducing inflammation may maximise fecundity and successful pregnancy outcome in women. Tweetable abstract: Lactobacilli prevent infection without inducing inflammation to maximise fertility and pregnancy outcome. Tweetable abstract: Lactobacilli prevent infection without inducing inflammation to maximise fertility and pregnancy outcome.